Uranyl(II) and Thorium(IV) Complexes of N-[o-Hydroxy Substituted (or H) Benzyl] Glycines - Bhallabh Karnatak, Kanti; Sekhar Pant, Chandra; Singh Dhami, Keshar; Bhallabh Melkani, Kirti; Chandra, Madhup (Asian Journal of Chemistry, 2010)
Several uranyl (II) and thorium(IV) complexes of N-[o-hydroxy substituted (or H) benzyl]glycines have been isolated from 50% (v/v) aqueous-DMSO or DMF medium in 1: 1 and 1: 2 molar ratios which were characterized by elemental analysis and spectral measurements.